Cryptic splicing: common pathological mechanisms involved in male infertility and neuronal diseases. Issue 3 (1st February 2022) - Aldalaqan, Saad; Dalgliesh, Caroline; Luzzi, Sara; Siachisumo, Chileleko; Reynard, Louise N; Ehrmann, Ingrid; Elliott, David J.
ABSTRACT: High levels of transcription and alternative splicing are recognized hallmarks of gene expression in the testis and largely driven by cells in meiosis. Because of this, the male meiosis stage of the cell cycle is often viewed as having a relatively permissive environment for gene expression. In this review, we highlight recent findings that identify the RNA binding protein RBMXL2 as essential for male meiosis. RBMXL2 functions as a "guardian of the transcriptome" that protects against the use of aberrant (or "cryptic") splice sites that would disrupt gene expression. This newly discovered protective role during meiosis links with a wider field investigating mechanisms of cryptic splicing control that protect neurons from amyotrophic lateral sclerosis and Alzheimer's disease. We discuss how the mechanism repressing cryptic splicing patterns during meiosis evolved, and why it may be essential for sperm production and male fertility.